N-octanoyl dopamine treatment exerts renoprotective properties in acute kidney injury but not in renal allograft recipients - Klotz, Sarah; Pallavi, Prama; Tsagogiorgas, Charalambos; Zimmer, Fabian; Zöllner, Frank G.; Binzen, Uta; Greffrath, Wolfgang; Treede, Rolf-Detlef; Krämer, Bernhard; Yard, Benito A.; Höger, Simone (Nephrology, dialysis, transplantation, 2016)
Background: N-octanoyl dopamine (NOD) treatment improves renal function when applied to brain dead donors and in the setting of warm ischaemia-induced acute kidney injury (AKI). Because it also activates transient receptor potential vanilloid type 1 (TRPV1) channels, we first assessed if NOD conveys its renoprotective properties in warm ischaemia-induced AKI via TRPV1 and secondly, if renal transplant recipients also benefit from NOD treatment. Methods: We induced warm renal ischaemia in Lewis, wild-type (WT) and TRPV1-/- Sprague-Dawley (sd) rats by clamping the left renal artery for 45 min. Transplantations were performed in allogeneic and syngeneic donor–recipient combinations (Fisher to Lewis and Lewis to Lewis) with a cold ischaemia time of 20 h. Treatment was instituted directly after restoration of organ perfusion. Renal function, histology and perfusion were assessed by serum creatinine, microscopy and magnetic resonance imaging (MRI) using arterial spin labelling (ASL). Results: NOD treatment significantly improved renal function in Lewis rats after warm ischaemia-induced AKI. It was, however, not effective after prolonged cold ischaemia. The renoprotective properties of NOD were only observed in Lewis or WT, but not in TRPV1-/- sd rats. Renal inflammation was significantly abrogated by NOD. MRI-ASL showed a significantly lower cortical perfusion in ischaemic when compared with non-ischaemic kidneys. No overall differences were observed in renal perfusion between NOD- and NaCl-treated rats. Conclusions: NOD treatment reduces renal injury in warm ischaemia, but is not effective in renal transplant in our experimental animal models. The salutary effect of NOD appears to be TPRV1-dependent, not involving large changes in renal perfusion.
Gesehen am 25.04.2019